Neobanks New Challenge in the Financial Peruvian Market - Giudice Baca, Victor (2020)
Competition between Traditional Banks with Electronic Banks Fintech, Shadow Banking and Neobanks is an intense scenario in The European Union, USA, Japan, Brazil and Argentina. Neobanks allied to Big Banks of The USA and Europe have been transformed into Transnational Banks. They may appear in Peru year 2020. Three of them have already asked for license to Peruvian Supervising Autorithy SBS. Present research has investigated 17 Neobanks finantial operations, mainly innovative and successful in developed markets. Research sources have been International Consulting Firms in Banking and Finance.